Hva betyr samfunnsansvar for bedrifter som importerer råvarer fra utviklingsland? - Ingebrigtsen, Sara Kristine (Universitetet i Nordland, 2012)
Studentarbeid i økonomi og ledelse (bachelorgrad) - Universitetet i Nordland, 2012 The purpose of this study has been to study which codes of ethics Norwegian corporations that import raw material from developing countries have to their suppliers, and how they are making sure that the codes are being followed. I have reviewed relevant literature on CSR, codes of ethics and globalization in order to address the specific issues of this paper. To determine this I decided to compare two large Norwegian companies, Kaffehuset Friele which is Norway’s largest coffee producer, and Nidar which is the largest supplier in Norway of candy. Both companies have very informative websites, so I chose to only use the internet to get the information I needed. Then I used the data I had collected and compared the companies to see whether there were similarities and differences in their way of working with social responsibility, and so I compared my findings to the literature I have used and ended with a conclusion. The main conclusion from this study is that Norwegian corporations that imports raw material from developing countries take a social responsibility and do follow up their suppliers, but that they still have some way to go in order to have 100 % control of the supply chain.